The Arctic vessel Gjøa - Kjær, Kjell-G. (Polar Record, 2005)
The Arctic vessel Gjøa was the first ship that sailed through the Northwest Passage from the Atlantic to the Pacific Ocean, a voyage captained by Roald Amundsen. Gjøa was launched in 1872 and for 10 years was captained by Asbjørn Sexe while transporting fish products from northern Norway to ports on the west coast. She was wrecked in 1882 and sold to Captain Hans Chr. Johannesen, under whose ownership she sailed for 18 years as a sealer in Arctic waters including voyages to the Kara Sea, Novaya Zemlya, Franz Josef Land, Svalbard, and northeast Greenland. In 1892 she was the expedition ship for the Axel Hamberg expedition to Spitsbergen, and in 1900 she was a tender for the Svensksund expedition to Spitsbergen. The following year she was sold to Amundsen. On 17 June 1903, Amundsen and his companions sailed from Kristiania (present-day Oslo) and three years later they completed the transit of the Northwest Passage. In 1909 Gjøa was put ashore in the Golden Gate Park in San Francisco. In 1972 — 100 years after Gjøa was launched — she returned to Oslo and was made a permanent exhibit outside the maritime museum (Norsk Sjøfartsmuseum), where she can be seen today.